Design and analyze various types of water level sensor in a tank system - 433758 Loh, Tze Yen (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 2003